29. Efficacy of Sevoflurane for treatment of focal RSE in ICU: Case report. Issue 12 (December 2017) - Scarpino, M.; Lanzo, G.; Grippo, A.; Carrai, R.
Abstract : Inhalational halogenated anaesthetics (IA) have been rarely used for super-refractory status epilepticus (SRSE) treatment. Halogenated (sevoflurane in particular) have not been used in intensive care unit (ICU) or refractory status epilepticus (RSE) treatment before conventional intravenous anaesthetic drugs. We report a case of a patient with a severe liver failure (Child-Pugh C cirrhosis), who presented a focal motor RSE in which sevoflurane has been used as the first anaesthetic treatment, because of its fewer side effects compared to other anaesthetic drugs. Sevoflurane was delivered with the MIRUS™ system (Pall-Medical, Dreieich, Germany), a new device manufactured for IA (isoflurane/desflurane/sevoflurane) administration in critically ill patients. The increase of the sevoflurane minimum-alveolar-concentration (MAC) from 0.3% to 1.0% resulted in the resolution of the ictal activity as detected by the continuous EEG monitoring. The patient was discharged 48 h later, after a complete neurological recovery. Sevoflurane could be used in ICU not only for SRSE but also for RSE treatment, in patients in which conventional intravenous anaesthetic drugs are contraindicated as in case of severe hepato-renal failure. Sevoflurane presents a dose-dependent central nervous system effect, a high potency and moreover, emergence and orientation are significantly faster compared to isoflurane use.